Early Diffusion MR Imaging Findings and Short-Term Outcome in Comatose Patients with Hypoglycemia - Johkura, K.; Nakae, Y.; Kudo, Y.; Yoshida, T.N.; Kuroiwa, Y. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The relationship between the MR imaging features and clinical outcomes in patients with hypoglycemic encephalopathy has always been evaluated retrospectively. The aim of this study was to prospectively evaluate whether MR imaging features of patients presenting with hypoglycemic coma are predictive of short-term (1-week) outcomes. MATERIALS AND METHODS: Subjects were 36 consecutive patients with hypoglycemia who were in a comatose state on arrival at our hospital from April 2006 to March 2010. MR imaging findings on arrival in relation to the patients' clinical course after glucose infusion were evaluated. RESULTS: Thirteen of the 36 patients showed no MR imaging abnormalities on arrival. DWI revealed focal lesions involving the internal capsule in 13 patients and lesions involving bilateral hemispheric white matter in 10 patients. After glucose administration, the patients without lesions and patients with focal internal capsule lesions recovered completely within 1 day. However, patients with diffuse white matter lesions did not recover even within 1 week despite glucose administration. There was no statistical difference in the initial blood glucose levels among patients with the various types of MR imaging findings. CONCLUSIONS: On early MR imaging, hypoglycemic brain injury may first appear in the internal capsule and then spread into the hemispheric white matter. The absence of a lesion or the presence of a focal internal capsule lesion may suggest a good outcome. However, diffuse hemispheric white matter lesions may indicate a poor 1-week outcome.